Until the end of time [large type] : mind, matter, and our search for meaning in an evolving universe - Greene, B. (Brian), 1963- (Random House Large Print, 2020)
"From the world-renowned physicist, co-founder of the World Science Festival, and best-selling author of The Elegant Universe comes this utterly captivating exploration of deep time and humanity's search for purpose. Brian Greene takes readers on a breathtaking journey from the big bang to the end of time and invites us to ponder meaning in the face of this unimaginable expanse. He shows us how, from its original orderly state the universe has been moving inexorably toward chaos, and, still, remarkable structures have continually formed: the planets, stars, and galaxies that provide islands in a sea of disorder; biochemical mechanisms, including mutation and selection, animate life; neurons, information, and thought developed into complex consciousness which in turn gave rise to cultures and their timeless myths and creativity. And he describes, as well, how, in the deep reaches of the future, the nature of the universe will threaten the existence of matter itself. Through a series of nested stories Greene provides us with a clearer sense of how we came to be, a finer picture of where we are now, and a firmer understanding of where we are headed. Taken together, it is a completely new perspective on our place in the universe and on what it means to be human"--